Dynamic proteome in enigmatic preeclampsia: an account of molecular mechanisms and biomarker discovery - Mary, Sheon; Patil, Gouri V.; Kulkarni, Asmita V.; Kulkarni, Mahesh J.; Joshi, Sadhana R.; Mehendale, Savita S.; Giri, Ashok P. (Proteomics Clinical Applications, 2012)
The coevolution of genomics and proteomics has led to advancements in the field of diagnosis and molecular mechanisms of disease. Proteomics is now stepping into the field of obstetrics, where early diagnosis of pregnancy complication such as preeclampsia (PE) is imperative. PE is a multifactorial disease characterized by hypertension with proteinuria, which is a leading cause of maternal and neonatal morbidity and mortality occurring in 5-7% of pregnancies worldwide. This review discusses the probable molecular mechanisms that lead to PE and summarizes the proteomics research carried out in understanding the pathogenicity of PE, and for identifying the candidate biomarker for diagnosis of the disease.
Keywords: Hypertension; Oxidative stress; Pregnancy complication; Proteinuria

Glycated proteome: from reaction to intervention - Kulkarni, Mahesh J.; Korwar, Arvind M.; Mary, Sheon; Bhonsle, Hemangi S.; Giri, Ashok P. (Proteomics Clinical Applications, 2013)
Glycation, a nonenzymatic reaction between reducing sugars and proteins, is a proteome wide phenomenon, predominantly observed in diabetes due to hyperglycemia. Glycated proteome of plasma, kidney, lens, and brain are implicated in the pathogenesis of various diseases, including diabetic complications, neurodegenerative diseases, cancer, and aging. This review discusses the strategies to characterize protein glycation, its functional implications in different diseases, and intervention strategies to protect the deleterious effects of protein glycation.
Keywords: aging; Diabetes; Glycation; RAGE

Immune response to chemically modified proteome - Bhat, Shweta; Mary, Sheon; Banarjee, Reema; Giri, Ashok P.; Kulkarni, Mahesh J. (Proteomics Clinical Applications, 2014)
Both enzymatic and nonenzymatic PTMs of proteins involve chemical modifications. Some of these modifications are prerequisite for the normal functioning of cell, while other chemical modifications render the proteins as neo-self antigens, which are recognized as non-self leading to aberrant cellular and humoral immune responses. However, these modifications could be a secondary effect of autoimmune diseases, as in the case of type I diabetes, hyperglycemia leads to protein glycation. The enigma of chemical modifications and immune response is akin to the chick-and-egg paradox. Nevertheless, chemical modifications regulate immune response. In some of the well-known autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematosus, and multiple sclerosis, chemically modified proteins act as autoantigens forming immune complexes. In some instances, chemical modifications are also involved in regulating immune response during pathogen infection. Further, the usefulness of proteomic analysis of immune complexes is briefly discussed.
Keywords: Autoantibody; Autoimmune diseases; Immune complex; Immunoproteomics; PTMs

Differential accumulation of vimentin fragments in preeclamptic placenta - Mary, Sheon; Kulkarni, Mahesh J.; Mehendale, Savita S.; Joshi, Sadhana R.; Giri, Ashok P. (Cytoskeleton, 2017)
Preeclampsia is a pregnancy complication that is the result of abnormal placentation because of inadequate trophoblast invasion into spiral arteries that prevent normal blood flow to the placenta. We report the alteration in vimentin protein proteolysis in placenta of normotensive and preeclamptic women, which is known to have a role in many physiological functions other than its major function in the structural integrity of the cell. Placental proteome from normotensive (n=25) and preeclamptic pregnancies (n=25) showed eight differentially accumulated protein spots of vimentin (proteolytic fragments) by two-dimensional electrophoresis. Immunoblots of normotensive and preeclamptic placenta revealed a difference in proteolytic processing of vimentin. In particular, lower molecular weight vimentin fragments of 32 and 20 kDa were 3.3 and 2.6-fold (p<0.0001) higher, respectively, in preeclampsia compared with normotensive placenta.

Placental proteomics provides insights into pathophysiology of pre-eclampsia and predicts possible markers in plasma - Mary, Sheon; Kulkarni, Mahesh J.; Malakar, Dipankar; Joshi, Sadhana Ramchandra; Mehendale, Savita S.; Giri, Ashok P. (Journal of Proteome Research, 2017)
Pre-eclampsia is a hypertensive disorder characterized by the new onset of hypertension >140/90 mmHg and proteinuria after the 20th week of gestation. The disorder is multi-factorial and originates with abnormal placentation. Comparison of the placental proteome of normotensive (n=25) and pre-eclamptic (n=25) patients by gel-free proteomic techniques, identified a total of 2145 proteins in the placenta of which 180 were differentially expressed (>1.3 fold, p<0.05). Gene ontology enrichment analysis of biological process suggested that the differentially expressed proteins belonged to various physiological processes such as angiogenesis, apoptosis, oxidative stress, hypoxia, placental development, which are implicated in the pathophysiology of pre-eclampsia. Some of the differentially expressed proteins were monitored in the plasma by multiple reaction monitoring (MRM) analysis, which showed an increase in Apolipoprotein AI and AII in gestational week 26-30th (2-fold, p<0.01) while haptoglobin and hemopexin decreased in gestational week 26-30th and 40th week/at delivery (1.8 fold, p<0.01) in pre-eclamptic patients. This study provides a proteomic insight into the pathophysiology of pre-eclampsia. Identified candidate proteins can be evaluated further for the development of potential biomarkers associated with pre-eclampsia pathogenesis.

Polymerization-incompetent uromodulin in the pregnant stroke-prone spontaneously hypertensive rat - Mary, Sheon; Small, Heather Yvonne; Siwy, Justyna; Mullen, William; Giri, Ashok; Delles, Christian (Hypertension, 2017)
The kidney is centrally involved in blood pressure regulation and undergoes extensive changes during pregnancy. Hypertension during pregnancy may result in an altered urinary peptidome that could be used to indicate new targets of therapeutic or diagnostic interest. The stroke-prone spontaneously hypertensive rat (SHRSP) is a model of maternal chronic hypertension. Capillary electrophoresis-mass spectrometry was conducted to interrogate the urinary peptidome in SHRSP and the control Wistar-Kyoto strain at three time points: prepregnancy and gestational days 12 and 18. The comparison within and between the Wistar-Kyoto and SHRSP peptidome at all time points detected 123 differentially expressed peptides (fold change >1.5; P<0.05). Sequencing of these peptides identified fragments of collagen a-chains, albumin, prothrombin, actin, serpin A3K, proepidermal growth factor, and uromodulin. Uromodulin peptides showed a pregnancy-specific alteration in SHRSP with a 7.8-fold (P<0.01) and 8.8-fold (P<0.05) increase at gestational days 12 and 18, respectively, relative to the Wistar-Kyoto. Further investigation revealed that these peptides belonged to the polymerization-inhibitory region of uromodulin. Two forms of uromodulin (polymerization competent and polymerization incompetent) were found in urine from both Wistar-Kyoto and SHRSP, where the polymerizationincompetent form was increased in a pregnancy-specific manner in SHRSP. Nifedipine-treated pregnant SHRSP showed only polymerization-competent uromodulin, indicating that calcium may be mechanistically involved in uromodulin polymerization. This study highlights, for the first time, a potential role of uromodulin and its polymerization in hypertensive pregnancy.
Keywords: Hypertension; Kidney; Nifedipine; pregnancy; uromodulin

Resistin mediates sex-dependent effects of perivascular adipose tissue on vascular function in the shrsp - McNeilly, Sarah; Small, Heather Y.; Mary, Sheon; Sheikh, Adam; Delles, Christian (20th Annual Meeting of the Scottish-Cardiovascular-Forum, 2017)

Tubulointerstitial nephritis antigen-like 1 protein is downregulated in the placenta of pre-eclamptic women - Mary, Sheon; Kulkarni, Mahesh J.; Mehendale, Savita S.; Joshi, Sadhana R.; Giri, Ashok P. (Clinical Proteomics, 2017)
Background: Tubulointerstitial nephritis antigen-like 1 protein (TINAGL1), is a matricellular protein, known to play role in cell adhesion and cell receptor interaction. Research related to TINAGL1 is limited to cell culture and animal models. Demonstration of TINAGL1 as a positive regulator of angiogenesis and its expression in the decidua of postimplantation mouse uterus, prompted us to validate its expression in human placenta during impaired angiogenesis in pre-eclamptic condition. Methods: Placental tissue from normotensive (n = 25) and pre-eclamptic (n = 25) pregnancies were used to study the differentially expressed proteins by two-dimensional gel electrophoresis and TINAGL1 protein was validated with Western blotting. Results: A total of 55 protein spots were differentially expressed (fold change > 1.5, p < 0.05), of which 27 were upregulated and 28 were downregulated in the pre-eclamptic placenta. TINAGL1 was found to be downregulated in pre-eclamptic compared to normotensive pregnant women. Conclusion: This is the first study reporting TINAGL1 to be present in human placenta and differentially expressed in pre-eclamptic condition. The functional role of TINAGL1 in association to human pregnancy needs to be explored further.